Uncertainty in the sphere of the Industry 4.0 – potential areas to research - Magruk, Andrzej (Business, Management and Economics Engineering, 2016)
The world stands on the threshold of a new age of technology, which will launch a fourth industrial revolution (Industry 4.0). According to this idea, web-based network will support smart factories at every stage of the work on the product, from design through to servicing and recycling. It is a vision of a world in which the real environment connects to the digital one using follows driving forces: Internet of things, cloud computing, big data, cyber-physical systems, and others. The Industry 4.0 concept is based on developing smart chains preparation based on communicating with each other means of production, products, components, plants, humans. Established in Germany, the concept of Industry 4.0, is the brainchild – its beginning reaches 2011. It is therefore fraught with high level of uncertainty in many aspects (economic, social, technological, legal, etc.). The main aim of this article is to analyze different dimensions of uncertainty regarding the Industry 4.0, both in terms of opportunities and threats. Due to the freshness of the topic and the great complexity of the Industry 4.0 phenomenon, the main aim of the article is to identify potential areas requiring the necessary research in order minimizing negative – today uncertain – effects occurring in both the design concept Industry 4.0 as well as during its functioning.